1999
DOI: 10.1128/jvi.73.12.10129-10136.1999
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Bovine Viral Diarrhea Virus RNA-Dependent RNA Polymerase

Abstract: Recombinant bovine viral diarrhea virus (BVDV) nonstructural protein 5B (NS5B) produced in insect cellshas been shown to possess an RNA-dependent RNA polymerase (RdRp) activity. Our initial attempt to produce the full-length BVDV NS5B with a C-terminal hexahistidine tag in Escherichia coli failed due to the expression of insoluble products. Prompted by a recent report that removal of the C-terminal hydrophobic domain significantly improved the solubility of hepatitis C virus (HCV) NS5B, we constructed a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 32 publications
5
55
0
Order By: Relevance
“…10,11,16 The remaining mutations have not been addressed previously including the so-called fingers and thumb subdomains of NS5B. 31,48 The designed mutations of the constructs were confirmed by nucleotide sequencing.…”
Section: Design Expression and Purification Of The Mutant Constructmentioning
confidence: 99%
“…10,11,16 The remaining mutations have not been addressed previously including the so-called fingers and thumb subdomains of NS5B. 31,48 The designed mutations of the constructs were confirmed by nucleotide sequencing.…”
Section: Design Expression and Purification Of The Mutant Constructmentioning
confidence: 99%
“…This mechanism has been observed in BVDV NS5B for initiation of RNA synthesis [21]. It was also found that both the copyback mechanism and the de novo mechanism for initiation of RNA synthesis might be present in the NS5B protein of CSFV and BVDV [7,13]. The fact that the CSFV NS5B has a TNTase activity, together with other data in this research and previous reports, increases this possibility that two mechanisms, copy-back and de novo, are compatible with each other in the CSFV viral genomic replication.…”
Section: Discussionmentioning
confidence: 97%
“…4B, lanes 2-4), followed by +RNA2 and +RNA3 (lanes 5-10). In contrast, +RNA4 and +RNA5 were poor competitors (lanes [11][12][13][14][15][16]. These results indicated that the CSFV NS5B protein bound the 3¢ UTR mainly through interaction with the 21 nucleotide bases at the terminal.…”
Section: Mapping Of the Ns5b-binding Site On The Csfv Genomementioning
confidence: 93%
See 1 more Smart Citation
“…With sequence analysis and analysis of the hydropathy profile, we found that the C-terminal part of NS5B contains a highly hydrophobic region which is predicted to be an anchoring domain (Lindenbach and Rice, 2001). It has been reported that their deletion increases the solubility of NS5B expressed in E. coli Lai et al, 1999;Tomei et al, 2000;Yamash ita et al, 1998;Zhong et al, 2000). Therefore, the effect of the Cterminal region was examined by constructing the expression plasmids, pET-NS5B 24 and pET-NS5B 24GAA, which lacked the C-terminal 24 amino acid residues.…”
Section: Expression and Purification Of The Recombinant Ns5b Proteinsmentioning
confidence: 99%